2017
DOI: 10.1177/2167696817690978
|View full text |Cite
|
Sign up to set email alerts
|

Relationships With Parents, Identity Styles, and Positive Youth Development During the Transition From Adolescence to Emerging Adulthood

Abstract: The purpose of this study was to examine the links between relationships with parents, identity styles, and positive youth development (PYD), conceptualized as "contribution" to self, family, and community, in Lithuanian youth during the transition from adolescence to emerging adulthood. In Study I, we sought to examine how positive relationships with parents predict contribution with the potential mediating role of autonomy-supportive parenting. Participants (N ¼ 153) filled a self-reported questionnaire in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 59 publications
(91 reference statements)
1
33
0
2
Order By: Relevance
“…An apparent need to contribute or reciprocate may manifest as favoring a parent over a friend when monetary rewards, but not social rewards, are at stake. Prior work indicates that friendships are predicated upon the need to feel understood by someone or having someone with whom to share thoughts (20,22,27). Consistent with this, participants in the present study indicated on a relationship quality measure that they could communicate their experiences and feelings more effectively with friend than parent, and that their friend can better relate to what they are experiencing than their parent.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…An apparent need to contribute or reciprocate may manifest as favoring a parent over a friend when monetary rewards, but not social rewards, are at stake. Prior work indicates that friendships are predicated upon the need to feel understood by someone or having someone with whom to share thoughts (20,22,27). Consistent with this, participants in the present study indicated on a relationship quality measure that they could communicate their experiences and feelings more effectively with friend than parent, and that their friend can better relate to what they are experiencing than their parent.…”
Section: Discussionsupporting
confidence: 79%
“…Preferences for parents in situations with financial outcomes may thus be driven by a need to contribute or reciprocate (21). By contrast, the apparent lack of a parent or friend preference in decisions with social outcomes may be due to the fact that some individuals prefer spending time with their parent and others with their friend, leading to a net zero preference at the group level (20,22). It is also important to consider that time spent with a close other is not necessarily synonymous with the concept of a social preference.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the seemingly monolithic importance of friends, parents also remain important in the lives of their young adult offspring. Like friends, parents also impact how young adults engage in real world risk taking behaviors and make decisions (Abaied & Emond, 2013;Carlson, 2014;Guassi Moreira & Telzer, 2018), refine existing identities (Kaniušonytė & Žukauskienė, 2018), and maintain mental wellbeing (Guassi Moreira & Telzer, 2015;Lucas-Thompson, 2014;Needham, 2008).…”
Section: Parents Versus Peers: Assessing the Impact Of Social Agents mentioning
confidence: 99%
“… 1 , 3 First symptoms often occur in early adolescence or the late teens, when most young people are about to disengage from their families and become more independent. 4 , 5 In Western society, many young people spend much of their time with friends, in school, and at activities of various kinds: surroundings that are often beyond parental control.…”
Section: Introductionmentioning
confidence: 99%